A chemically inert Rashba split interface electronic structure of C60, FeOEP and PTCDA on BiAg2/Ag(111) substrates - Maren C Cottin; Jorge Lobo-Checa; Johannes Schaffert; Christian A Bobisch; Rolf Möller; J Enrique Ortega; Andrew L Walter (New Journal of Physics, 2014)
The fields of organic electronics and spintronics have the potential to revolutionize the electronics industry. Finding the right materials that can retain their electrical and spin properties when combined is a technological and fundamental challenge. We carry out the study of three archetypal organic molecules in intimate contact with the BiAg _2 surface alloy. We show that the BiAg _2 alloy is an especially suited substrate due to its inertness as support for molecular films, exhibiting an almost complete absence of substrate–molecular interactions. This is inferred from the persistence of a completely unaltered giant spin-orbit split surface state of the BiAg _2 substrate, and from the absence of significant metallic screening of charged molecular levels in the organic layer. Spin-orbit split states in BiAg _2 turn out to be far more robust to organic overlayers than previously thought.